Performance of Risk Assessment Indices for the Prediction of Postmenopausal Osteoporosis - Original Investigation - Sibel Ünsal Delialioğlu; Kurtuluş Kaya; Zuhal Özişler; Sumru Özel (Galenos Yayinevi, 2009)
Aim: The purpose of this study was to determine the performance of osteoporosis risk assessment indices in identifying women with osteoporosis who has high risk for osteoporosis and who will undergo dual energy X-ray absorptiometry (DEXA). Material and Methods: Ninety-eight postmenopausal women aged 45 years and older (mean age 57.36±5.78 years) were included in the study. BMD was used for diagnosing osteoporosis at the proximal femoral and lumbar spine (L2-L4). The subjects were evaluated in terms of the risk for osteoporosis by using Osteoporosis Foundation (NOF), Osteoporosis Prescreening Risk Assessment (OPERA), Age, years after Menopause, age at MEnarche, Body mass index (AMMEB), National and Osteoporosis Screening Tool (OST). Sensitivity, specifity and the diagnostic value of the risk assessment indices were calculated. Results: The proportion of women with osteoporosis at the femoral neck (T skor ≤-2.5) was 14.3% (14/98) and, 33.7% (33/98) at the lumbar spine. The sensitivity, specifity and the diagnostic value of the risk assessment indices to identify osteoporosis at the femoral neck were found respectively %60-%62-%62 for NOF, %35-%71-%66 for OPERA, %80-%68-%69 for OST and %80-%68-%69 for AMMEB. At the lumbar spine these values were %42-%72-%62 for NOF, %12-%93-%66 for OPERA, %54-%76-%69 for OST and %60-%73-%69 for AMMEB. Conclusion: These results show that OST and AMMEB have high sensitivity for identifying femoral neck osteoporosis. Therefore all four indices have low sensitivity for identifing lumbar spine osteoporosis. In conclusion OST and AMMEB could be preferred as a screening test in clinical practice for identifying the femoral neck osteoporosis. (From the World of Osteoporosis 2009;15:21-5)